2018
DOI: 10.1101/320705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stiffness Sensing and Cell Motility: Durotaxis and Contact Guidance

Abstract: Mechanical properties of the substrate plays a vital role in cell motility. Cells are shown to migrate up stiffness gradient (durotaxis) and along aligned fibers in the substrate (contact guidance). Here we present a simple mechanical model for cell migration, by placing a cell on lattice models for biopolymer gels and hydrogels. In our model cells attach to the substrate via focal adhesions (FAs). As the cells contract, forces are generated at the FAs, determining their maturation and detachment. At the same … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Furthermore, the straight configuration of FCs that is augmented due to nonlinear elasticity can form a structural guide to direct cell migration. Many types of migrating cells exhibit directionally persistent migration along the direction of aligned elements [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the straight configuration of FCs that is augmented due to nonlinear elasticity can form a structural guide to direct cell migration. Many types of migrating cells exhibit directionally persistent migration along the direction of aligned elements [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the transport properties (e.g., macromolecule diffusivity) [32,[37][38][39][40][41][42][43][44][45][46] and mechanical properties (e.g., elastic moduli, bulk rheology, stress distribution, etc.) [14,16,18,35,[47][48][49][50][51][52][53] of biopolymer network, which are respectively crucial to the chemical and mechanical signalling between the cells, strongly depend on the network microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al. ( Feng et al., 2018 ) showed that if FA degradation is higher in the back than in the front and FAs mature under applied force, then a cell can durotact. Based on experimental observations, Novikova et al.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step toward more complex matrices, we have studied how cell spreading, elongation, and durotaxis are affected by inhomogeneity in substrate stiffness (uniform noise, Figures S4 A–C) and explored the effect of small-scale spatial inhomogeneities on cell elongation ( Figures S4 D–L). In our ongoing work, we are extending the model to better represent the fibrous and strain-stiffening properties of natural ECMs ( Hall et al, 2016 ; Han et al, 2018 ; van Helvert and Friedl, 2016 ) by incorporating discrete ECM models ( Feng et al., 2015 , 2018 ; Kim et al., 2017 ; Licup et al, 2015 ) with our cell-based models. Although the effect of traction forces propagates further into nonlinearly elastic, fibrous ECMs ( Ma et al., 2013 ), the key results of our model are based on increased stability of FAs on strained matrices and so, will likely still apply.…”
Section: Discussionmentioning
confidence: 99%